Antibody levels correlate with detection of Trypanosoma cruzi DNA by sensitive polymerase chain reaction assays in seropositive blood donors and possible resolution of infection over time. Issue 6 (25th September 2012) - Sabino, Ester C.; Lee, Tzong‐Hae; Montalvo, Lani; Nguyen, Megan L.; Leiby, David A.; Carrick, Danielle M.; Otani, Marcia M.; Vinelli, Elizabeth; Wright, David; Stramer, Susan L.; Busch, Michael
<x xml:space="preserve">Abstract</x> BACKGROUND: The clinical significance of anti‐Trypanosoma cruzi low‐level reactive samples is incompletely understood. Polymerase chain reaction (PCR)‐positive rates and antibody levels among seropositive blood donors in three countries are described. STUDY DESIGN AND METHODS: Follow‐up samples were collected from T. cruzi–seropositive donors from 2008 through 2010 in the United States (n = 195) and Honduras (n = 58). Also 143 samples from Brazil in 1996 to 2002, originally positive by three serologic assays, were available and paired with contemporary follow‐up samples from these donors. All samples were retested with Ortho enzyme‐linked immunosorbent assay (ELISA). PCR assays were performed on coded sample panels by two laboratories (Blood Systems Research Institute [BSRI] and American Red Cross Holland Laboratory [ARC]) that amplified kinetoplast minicircle DNA sequences of T. cruzi. RESULTS: PCR testing at BSRI yielded slightly higher overall sensitivity and specificity (33 and 98%) compared with those at the ARC (28 and 94%). Among seropositive donors, PCR‐positive rates varied by country (p < 0.0001) for the BSRI laboratory: Brazil (57%), Honduras (32%), and the United States (14%). ELISA signal‐to‐cutoff ratios (S/CO) were significantly higher for PCR‐positive compared to PCR‐negative donors (p < 0.05 for all comparisons). Additionally, PCR‐negative Brazilian donors exhibited greater frequencies of antibody decline over time versus PCR‐positive donors (p = 0.003). CONCLUSION: For all three countries, persistent DNA positivity correlated with higher ELISA S/CO values, suggesting that high‐level seroreactivity reflects chronic parasitemia. Significant S/CO declines in 10% of the PCR‐negative Brazilian donors may indicate seroreversion after parasite clearance in the absence of treatment.